THE TRADITION OF FEMALE CIRCUMCISION (THE INTEGRATION OF RELIGION AND CULTURE) - Abbas, Nurlaelah; Rahmatiah, St. (Jurnal Adabiyah, 2022)
The aims of this research are: the first, to describe the implementation of the female circumcision tradition in Jeneponto society, the second to describe the Islamic values ​​contained in the female circumcision tradition and the third to acquire a clear picture of the attitude and understanding of the people of Jeneponto about the tradition of female circumcision. This research is descriptive qualitative. This research was conducted in two ways, namely: library research and field research. The results of this study indicate that the tradition of female circumcision in Jeneponto society is carried out very lively as is the case with marriage traditions, starting with the preparation process such as deliberation, Korontigi events, to the circumcision reception. Various kinds of traditional rituals that have been carried out so far still reflect Islamic values ​​that are described in the form of religious understanding, solidarity and mutual cooperation as well as the value of beauty that is reflected in the entire series of traditional rituals. The attitude and understanding of Jeneponto society regarding the tradition of female circumcision which is an obligation for Muslims, and ancestral traditions that must be preserved. In addition, there is a social construction in the implementation of female circumcision, and the circumcision event is one of the gathering places. الملخص أهداف هذه الدراسة هي: أولا: وصف تنفيذ ختان الإناث في مجتمع جينيبونتو ، وثانيا: وصف القيم الإسلامية المتضمنة في ختان الإناث في جينيبونتو ، و ثالثا: الحصول على المواقف مفاهيم مجتمع جينيبونتو عن ختان الإناث في صورة واضحة. أما نوع البحث فهو نوعي وصفي. وأجريت الدراسة على طريقتين هما: البحث المكتبي والبحث الميداني. تظهر نتائج هذه الدراسة أن ختان الإناث في مجتمع جينيبونتو تم تنفيذه بشكل حفلات كبيرة كما هو الحال في احتفال وليمة العرس ، بدءا من عملية تحضيرية مثل المداولات ، وبرنامج الكورونتيةkorontigi حتى حفلات الختان. هناك مجموعة من الطقوس والتقاليد التى لا تخالف القيم الإسلامية مازالت تنفذ حتى الآن في شكل المفاهيم الدينية وتضامن عال والتعاون بين المجتمع وقيم الجمال المصور من طقوسها المعتادة. يعتبر ختان الإناث عند مجتمع جينيبونتو إلزاما للمسلمات، وتقاليد الأجداد التي يجب الحفاظ عليها. بالإضافة إلى ذلك ، هناك بناء اجتماعي في تنفيذ ختان الإناث حيث أنه وسيلة لصلة الأرحام بين المجتمع. الكلمات املفتاحية: تقاليد، ختان الإناث، الدين، الثقافة Abstrak Tujuan penelitian ini adalah : pertama, mendeskripsikan pelaksanaan tradisi khitan perempuan pada masyarakat Jeneponto kedua, mendeskripsikan nilai-nilai Islam yang terkandung dalam tradisi khitan perempuan dan ketiga, memperoleh gambaran yang jelas seperti apa sikap dan pemahaman masyarkat Jeneponto tentang tradisi khitan perempuan. Jenis penelitian ini adalah deskriptif kualitatif. Penelitian ini dilakukan dengan dua cara yaitu: penelitian kepustakaan dan penelitian lapangan. Hasil penelitian ini menunjukkan bahwa tradisi khitan perempuan pada masyarakat Jeneponto dilaksanakan dengan sangat meriah seperti halnya tradisi perkawinan, dimulai dengan proses persiapan seperti musyawarah, acara Korontigi, sampai pada acara resepsi khitanan. Berbagai macam ritual tradisi yang dilakukan selama ini masih mencerminkan nilai-nilai Islam yang terjabarkan dalam bentuk pemahaman religious, tingginya solidaritas dan gotong royong serta nilai keindahan yang tergambar dari seluruh rangkaian ritual adatnya. Sikap dan pemahaman masyarakat Jeneponto tentang tradisi khitan perempuan yang merupakan kewajiban bagi umat Islam, dan tradisi leluhur yang harus dilestarikan. Selain itu adanya konstruksi sosial dalam pelaksanaan khitan perempuan, serta acara khitan merupakan salah satu ajang silaturahmi. Kata Kunci: Tradisi; Khitan Perempuan; Agama dan Budaya